南開大學所藏姚培謙《李義山七律會意》之文獻問題考論: An Examination of Yao Peiqian’s Li Yishan qilü huiyi Preserved in Nankai University - 李, 宜學 (人文中國學報, 2018)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 清姚培謙爲清代李商隱詩箋注的四大家之一，以《李義山詩集箋注》爲世所知。然此書出版的前十二年，姚氏已先撰成《李義山七律會意》，專解李商隱七律，事卻罕爲人曉，書亦不甚流傳，今僅北京清華大學與天津南開大學兩校圖書館、當代藏書家黄裳先生庋有刻本，而俱不出借，外人難睹其詳。但據姚氏自云，其撰《李義山詩集箋注》時，嘗“取《會意》覆勘，十易二三”；換言之，《李義山七律會意》的不少見解仍匯入了《李義山詩集箋注》，成爲有機整體的一部份。對此少作，姚氏顯然十分珍視，並未輕易悔之，準此，則該書之重要性不言可喻矣！職是，筆者乃輾轉取得南開大學圖書館版《李義山七律會意》之影像檔，詳加考論，撰成此文。首論“成書與版式”，次論“取《會意》覆勘，十易二三”之説，冀完整梳理其版本問題、比對《李義山七律會意》與《李義山詩集箋注》前後箋注差異，俾爲進一步研究其箋注內涵奠定較爲扎實的文獻基礎。 Yao Peiqian (1693-1766) won renown as one of the four eminent Qing- dynasty annotators of Li Shangyin’s poetry because of his Li Yishan shiji jianzhu (An Annotated Edition of Li Shangyin’s Poems). Twelve years before the publication of this book, however, Yao had already completed a book entitled Li Yishan qilü huiyi (A Comprehensive Commentary on the Heptasyllabic Regulated Verse of Li Shangyin), a book devoted exclusively to the explanation of Li’s heptasyllabic regulated verse. This earlier work was not well known and not widely circulated. This book is held in only two libraries, namely Tsinghua University library in Beijing and Nankai University library in Tianjin. In addition, a woodblock printed copy is in the possession of a contemporary collector Mr. Huang Shang. All three copies are not available for loan and therefore not accessible to outsiders. According to Yao, when he wrote Li Yishan shiji jianzhu he “proofread the texts against Li Yishan qilü huiyi and changed two to three tenths of the content of the Jianzhu.” In other words, a significant amount of the Huiyi content was adopted in the Jianzhu and became an integral component of it. Obviously Yao cherished this early work very much and did not abandon it thoughtlessly. This reveals the importance of this book. For this reason, the author of the present essay made an effort to acquire the image files of this book preserved in Nankai University Library, carefully studied it, and wrote this essay. It begins with a section on “the making of the book and its layout,” which is followed by a discussion of what Yao said about “proofreading the texts against Li Yishan qilü huiyi and changing two to three tenths of the content of the Jianzhu.” These tasks are an attempt to conduct a comprehensive study of the issues concerning editions and a comparison of the respective annotations in these two books, in order to lay a solid textual foundation for further studies on the content and meaning of these annotations.